Sociolinguistics factors influencing student's interest in second language acquisition / Muhammad Fais Isa - Isa, Muhammad Fais (2014)
This study investigated on sociolinguistic factors which are age, gender and socioeconomic status that influence student's interest towards learning the second language. The sample of this study involved 100 secondary school students from various schools in Selangor. The study employed one system of collecting data, a set of questionnaire. The findings in this study indicate that the sociolinguistic factors do influence the student's interest in learning the second language. The result from this study could help language teachers to develop new approaches in teaching the second language.